Hubungan Higiene Sanitasi dengan Kualitas Mikrobiologis pada Olahan Minuman Serbuk (Studi di Wilayah Kerja Puskesmas Gunungpati Semarang) - Yuni Purwati; Praba Ginandjar; Nissa Kusariana; Retno Hestiningsih (Jurnal Ilmiah Mahasiswa, 2020)
Background : Processed beverage powder is a drink that comes from fruit juice with a variety of flavors. Poor processing of powdered drinks can cause contamination, such as contamination of Coliform bacteria, Escherichia coli and fungi, which if consumed can cause diarrhea. The purpose of this research is to analyze correlations between hygiene sanitation and microbiological quality of powdered drink processed in Elementary School and Madrasah Ibtidaiyah in Gunungpati Public Health Center Semarang). Methods : This is an observational analytic study with cross sectional study design. The samples were 70 participants consists of 35 samples processed powdered drinks and 35 ready to drink samples . Data were analyzed using Chi Square and Mantel Haenszel. The result showed that 23 samples (65,7%) of processed powdered drinks were contaminated with Coliform, 22 samples (62,9%) were contaminated with Escherichia coli and 4 samples (11,4%) contaminated fungus. While 5 samples (14,3%) of drink powder contaminated with Escherichia coli. Result : This study showed correlation between personal hygiene and microbiological quality of processed powdered drinks b (p=0,023), but has no correlation between personal hygiene and microbiological quality of processed powdered drinks of an outside canteen (p=0,236). Mantel Haenszel test showed correlation between personal hygiene and microbiological quality of processed powdered drinks of inschool canteen and outside canteen (p=0,013). There is no relation between equipment sanitation with micorbiological quality of processed powdered drinks of inschool canteen (p=1) and outside canteen (p=1) and p value Mantel Haenszel 0,971. There is no relation between sanitation and microbiological quality of processed powdered drinks of inschool canteen (p=0,371) and outside canteen (p=1) and p value of Mantel Haenszel was 0,783.Conclusion : Most of the powder drink preparations were found to be positive Coliform and Escherichia coli, but a small percentage of processed powder drink contaminated with fungus